The Long-Term Effects of Denominational Secondary Schools - Pusztai, Gabriella (European Journal of Mental Health, 2007)
In the present study we examined the graduate students of higher educational institutions with Hungarian as the language of teaching in Hungary, Rumania and the Ukraine. We were interested in seeing whether divergences could be traced, years after graduation, among students coming from certain secondary school sectors. Our results revealed that the more advantageous situation of former denominational high school students could be detected especially in the attitude to one’s work, the work concept of serving the common good, and the consumption of intellectual high culture in the traditional sense. These achievements of former denominational school students could not be explained with their social status, since these young people, in many respects, are more disadvantaged than the average. However, their value system and relationship network, and most of all their religiosity have a characteristic aspect. In regression models, we matched the strength of the seemingly significant explanations in the two-variable analysis. On the basis of the matching, we found that minding the influence of other explanations, regarding the readiness of entering service, the work concept of seeking social utility, as well as time spent on reading, sector-effect (effect of school maintainer) carries a very remarkable weight. After the passing of denominational school-years the personal or small-community worship can also inspire the formation or observance of this type of work concept, the attendance of students’ extracurricular tasks and the classical intellectual leisure time habits.